Criminal Acts of Persecution in the Perspective of Islamic Criminal Law and the Criminal Code: A Comparative Analysis of Concepts and Sanctions - Fery Dianta Ginting; Mhd Yadi Harahap (Jurnal Cendikia ISNU SU, 2025)
The crime of persecution is a crime against the human body that has a direct impact on the protection of human rights, a sense of justice, and social order, so that its regulation is an important issue in criminal law. Differences in the applicable legal system affect how an act is qualified as persecution and how criminal sanctions are imposed on the perpetrator. This paper aims to analyze comparatively the concept of the criminal act of persecution and its sanctions from the perspective of Islamic Criminal Law and the Criminal Code, as well as assess the relevance of the normative values contained in it for the development of national criminal law. This study uses normative legal research methods with legislative, conceptual, and comparative approaches. The legal materials used include laws and regulations, sources of Islamic law, as well as relevant legal doctrines and literature, which are analyzed qualitatively by prescriptive-analytical methods. The results of the discussion show that the Criminal Code views persecution as a violation of public order and the legal interests of the state with the imposition of criminal sanctions that are repressive and state-centric, so that the role of victims in the criminal process is relatively limited. Islamic Criminal Law views persecution as a jinayah against the human body that emphasizes the principles of balance, proportionality, and protection of the rights of victims through the concepts of qishash and diyat, as well as opening up space for forgiveness and the restoration of social relations. The conclusion of this study confirms that the comparison of the two legal systems shows a significant difference in the criminal paradigm, where the values of substantive justice and restorative orientation in Islamic Criminal Law have important relevance to be used as a normative reference in the reform of national criminal law, especially in the regulation of criminal acts of persecution that are more just and humane.